Aging and the haptic perception of 3D surface shape - Norman, J. Farley (Springer-Verlag, 2010)
Two experiments evaluated the ability of older and younger adults to perceive the three-dimensional (3D) shape of object surfaces from active touch (haptics). The ages of the older adults ranged from 64 to 84 years, while those of the younger adults ranged from 18 to 27 years. In Experiment 1, the participants haptically judged the shape of large (20 cm diameter) surfaces with an entire hand. In contrast, in Experiment 2, the participants explored the shape of small (5 cm diameter) surfaces with a single finger. The haptic surfaces varied in shape index (Koenderink, Solid shape, 1990; Koenderink, Image and Vision Computing, 10, 557–564, 1992) from −1.0 to +1.0 in steps of 0.25. For both types of surfaces (large and small), the participants were able to judge surface shape reliably. The older participants’ judgments of surface shape were just as accurate and precise as those of the younger participants. The results of the current study demonstrate that while older adults do possess reductions in tactile sensitivity and acuity, they nevertheless can effectively perceive 3D surface shape from haptic exploration.